Organizational Communication of Miftahul Jannah Raya Badan Kenaziran Masjid (BKM) in Management of in Mosque Padang Lawas Regency - Hasibuan, Yusri Yenni; Rubino, Rubino; Kustiawan, Winda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze (1) organizational communication of the nazirite agency of the Miftahul Jannah grand mosque in the management of mosque in Padang Lawas regency, (2) communication activities of the mosque’s nazirite agency (BKM) in the Miftahul Jannah Grand Mosque in Padang Lawas Regency, (3) communication barriers to the organization of the mosque nazir mosque (BKM) Raya Miftahul Jannah in the management of mosque in the district of Padang Lawas. This researcher uses a qualitative approach method. Data collecniques used are interviews, documentation, field notes. The information consisted of the chairman of the miftahul jannah mosque, the secretary of the miftahul jannah mosque, the advisor of the miftahul jannah mosque, the mifthaul jannah mosque staff. The results of the study are the first organizational communication interaction format, interpersonal communication, interpersonal communication goals, interpersonal relationships, small group communication, public communication, organizational communication climate, mosque management. Second, the communication activies of the BKM organization are very effective with this communication among BKM. By referring to the ideas, ideas and creativity possessed by organizational communication activities, by maintaining the cohesiveness of fellow BKM in any case. Activities used are formal communication success factors, organizational communication flows. Third, communication barriers of the BKM organization in managing the mosque. The obstacle is not too communication, BKM is very effective, and in terms of mosque facilities, it is supported by the surrounding community.